Fenomena Stockholm Syndrome dalam Drama 3 Nen A Gumi Karya Komuro Naoko dan Suzuki Yuma - Rabullizat, M Refy; Yuliani Giri, Ni Luh Kade; Ratna Dian Aryani, Made (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2024)
This research is titled "The Phenomenon of Stockholm Syndrome in the Drama 3 Nen A Gumi: Ima Kara Mina-san wa, Hitojichi Desu by Komuro Naoko and Suzuki Yuma". The aim of this research is to determine several factors that cause stockholm syndrome and its symptoms that appear in the drama 3 Nen A Gumi: Ima Kara Mina-san wa, Hitojichi Desu by Komuro Naoko and Suzuki Yuma. Qualitative method is used in this research. This research uses literary psychology theory from Wellek & Warren (1989:90), Stockholm syndrome theory from Graham, et al (2015) and behavioristic theory from B.F. Skinner (1953). The results of this research shows that, Stockholm syndrome symptoms in the drama 3 Nen A Gumi: Ima Kara Mina-san wa, Hitojichi Desu by Komuro Naoko and Suzuki Yuma is caused by the hostages`s compulsion to adjust their feeling to the conditions caused by hostage taker and begins to show mercy to the hostage taker when he shows kindness from time to time. The conditions caused by the hostage taker include (1) violence, (2) prohibition on running away, (3) prohibition on contact with the outside world, and (4) the hostage taker showing kindness. Then the symptoms of Stockholm syndrome that the hostages experienced include (1) Feeling sympathy for the hostage taker, (2) Having trust in the hostage taker, and (3) protecting the hostage taker